Improved logarithmic phase mask to extend the depth of field of an incoherent imaging system - Zhao, Hui; Li, Qi; Feng, Huajun (Optics letters, 2008)
A logarithmic phase mask was proposed in 2001, and the depth extension effect was proved at the same time. Three years later, in 2004, further research on that kind of mask obtained more results. This valuable work can be found in two papers [Proc. SPIE 4471, 272 (2001) and Appl. Opt. 43, 2709 (2004)]. We reviewed the papers carefully and made simple modifications to that mask. The modified phase mask still had the logarithmic form, but the simulation results demonstrated that it was superior to the original one.